Broun, William. William Broun to Edwin Broun, Berryville, VA, November 7, 1862 - Broun, William (Valdosta State University Archives and Special Collections, 2020., 1862)
Camp near Berryville November 7th 1862 Dear Pa, As I have a favorable opportunity of writing by Capt. Ayer who has been discharged I embrace it with a good deal of satisfaction as I do not always know that my letters reach home when written.
Letter from William Broun to his father Edwin Broun. Near Berryville, Virginia, November 7, 1862. 3 pages on two sheets of paper.
Keywords: American Civil War (1861-1865); Broun, Edwin, 1819-1904; Broun, William, Captain, 1842-1908; Personal correspondence; Rice, Zachariah Armstead, 1822-1890; Virginia--Berryville; Virginia--Northumberland County; Virginia; Letters